Chiron Approach for the Total Synthesis of Brevipolide M - Liu, Yang; Zhao, Ziyang; Hu, Chao; Zhao, Chuanfang; Liu, Jun; Du, Yuguo (Synlett, 2022)
An efficient stereoselective synthesis of brevipolide M was established in 13 linear steps and 17.8% overall yields based on chiron approach. The key steps of our synthesis involved tandem Wittig olefination–tetrahydrofuran cyclization and sequential ring-closing metathesis (RCM)–double-bond migration in one-pot processes.
Keywords: brevipolide M; 5,6-dihydro-α-pyrone; total synthesis; d-mannofuranose diacetonide; chiron approach